Evaluation of Lifelong Work Satisfaction among Former Postal Service Workers - Niska, Miira; Prakash, K.C; Siukola, Anna; Kosonen, Hanna; Luomanen, Jari; Lumme-Sandt, Kirsi; Neupane, Subas; Nikander, Pirjo; Nygård, Clas-Håkan (Nordic Journal of Working Life Studies, 2020)
While policymakers emphasize the need to delay retirement age, numerous traditional industries, among them postal services, emphasize the need for employee downsizings. These can be contradictory needs. Downsizings can reduce work life satisfaction (WLS) among workers, and reduced WLS can decrease willingness to delay retirement age. In this cross-sectional study, we explore WLS trajectories of former postal service workers by analyzing quantitative survey data (N = 201) and qualitative interview data (N = 40). In the data, workers aged 50–67 years evaluate their lifelong work satisfaction. The results of the quantitative and the qualitative study complement and mirror each other. Same trajectories of WLS were identified in both data. One-third of the survey respondents reported decreasing WLS, which according to the qualitative data relates to employee downsizings. The article highlights the importance of acknowledging contextual elements of work satisfaction measurement and the benefits of combining methodological traditions to understand the longer-term dynamics involved